Administrative measures to prevent and tackle crime: legal possibilities and practical applications in EU member states - Spapens, A. C.; Peters, Maaike; Daele, Dirk van (Eleven International Publ., 2015)
Criminals and persons involved in serious and organized crime often do not limit their activities to purely illegal ones such as drug trafficking, fraud or property crimes. They also invest money in legal activities and businesses, for instance to exploit the revenues of their crimes or to generate a legal income. Criminals may establish or take over a construction company and then tender for government contracts. The 'business processes' of most types of organized crime also require legal facilities. Authorities thus have a particular interest in preventing criminals from either using the economic infrastructure to acquire a legal income or from misusing businesses to facilitate crimes and applying their criminal proceeds towards this purpose. An administrative approach applied in addition to or coordinated with the traditional instruments of criminal law is a potentially powerful tool to prevent and combat serious and organized crime. 0In 2011, the European Commission awarded an ISEC grant to the Dutch Ministry of Security and Justice (coordinator) to conduct a 'study on the potential for information exchanges between administrative bodies and traditional law enforcement organizations to support the use of administrative measures within EU Member States and at EU level'. Tilburg University (the Netherlands) and the Catholic University of Leuven (Belgium) conducted this research, supported by the Belgian Home Affairs Ministry. The underlying report is the result of this ISEC grant